Exploring Alcohol and Substance Addiction among Syrian Migrants in Turkey: A Qualitative Study Integrating Perspectives of Addicts, Their Relatives, Local and National Institutions - Taşdemir, Mustafa; Küçükali, Hüseyin; Uçar, Abdullah; Sur, Haydar (Addicta: The Turkish Journal on Addictions, 2021)
Turkey is the country that hosts most migrants worldwide. Although migrants are a risk group for alcohol and substance addiction (ASA), literature is limited. This study aims to explore and identify the present state and influencing factors of ASA among Syrian migrants in Turkey by integrating perspectives of addicts, their relatives, and local and national institutions. This qualitative study was designed by the grounded theory approach and took place in 5 cities in Turkey between 2018 and 2019. It is composed of 4 focus group discussions with 77 informants from local governmental, non-governmental, and academic organizations; 11 key person interviews with heads of national organizations; and in-depth interviews with 45 addicted Syrian migrants and 21 relatives. Themes that emerged from the data are characteristics of addicted migrants, types of addictions, predisposing and exacerbating factors, preventing factors, obtaining alcohol and substances, manners of use, consequences of use, public services and utilization of them, and the experiences of addicted migrants. The findings of this study provide guidance for future research and policies. Addicted migrants have awareness and motivation to quit but face many environmental barriers. Activities of institutions in Turkey on ASA in Syrian migrants are insufficient. Specific, well-coordinated action is needed. It should also utilize Syrian human resources.